2007
DOI: 10.1590/s0103-50532007000800020
|View full text |Cite
|
Sign up to set email alerts
|

Cohalogenation of alkenes with DMF: an easy vicinal haloformyloxylation reaction

Abstract: A reação de alquenos com o ácido tricloro-isocianúrico ou N-bromo-sacarina ou I 2 / Fe 2 (SO 4 ) 3 na presença de DMF, seguida de tratamento em meio aquoso, leva à formação dos respectivos β-halo-formatos com alta regio-e estereosseletividade.The reaction of alkenes with trichloroisocyanuric acid or N-bromosaccharin or I 2 / Fe 2 (SO 4 ) 3 in the presence of DMF followed by aqueous work-up led to the corresponding β-haloformate in high regio-and stereoselectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 5 publications
0
10
0
1
Order By: Relevance
“…Since TsNBr 2 is a good oxidizing agent, 24 we envisioned that alcohols could directly be transformed into esters by carrying out the reaction in presence of an alcohol. We found that treatment of an alcohol (1 mmol) with 2.7 equivalents of TsNBr 2 in presence of five equivalents of K 2 CO 3 in a solvent mixture of acetonitrile/methanol (5:1) provided the corresponding methyl ester in a maximum yield of 75-88% (18). 27 Both aromatic and aliphatic alcohols could be transformed into the corresponding esters in moderate to high yields.…”
Section: Oxidative Esterification Processmentioning
confidence: 95%
See 1 more Smart Citation
“…Since TsNBr 2 is a good oxidizing agent, 24 we envisioned that alcohols could directly be transformed into esters by carrying out the reaction in presence of an alcohol. We found that treatment of an alcohol (1 mmol) with 2.7 equivalents of TsNBr 2 in presence of five equivalents of K 2 CO 3 in a solvent mixture of acetonitrile/methanol (5:1) provided the corresponding methyl ester in a maximum yield of 75-88% (18). 27 Both aromatic and aliphatic alcohols could be transformed into the corresponding esters in moderate to high yields.…”
Section: Oxidative Esterification Processmentioning
confidence: 95%
“…This protocol is more effective compared to other protocols involving bromo-organic compounds, such as N,N-dibromobenzenesulfonamide 17 and N-bromosaccharin. 18 The idea was then extended to prepare bromoacetoxy products by using acetic acid as solvent. 16 The desired products were isolated in up to 95% yield by adding TsNBr 2 to the stirred solution of olefin in acetic acid under nitrogen atmosphere (Scheme 13).…”
Section: Bromoformyloxylation and Bromoacetoxylation Of Olefinsmentioning
confidence: 99%
“…13 Já a co-halogenação de alquenos em presença de água seguida de adição de base fornece epóxidos em altos rendimentos, 14 enquanto que a co-halogenação em presença de NaCl se mostrou uma metodologia eficiente, limpa e bastante segura para a preparação de dicloro-alcanos vicinais. 15 Embora o TCCA seja um reagente bastante utilizado em diversas transformações orgânicas, são raros os exemplos que envolvem a cloração de anéis aromáticos; estes, por sua vez, incluem reações radicalares, catalisadas por ácidos ou líquidos iônicos.…”
Section: Introductionunclassified
“…In 2013, Studer et al have reported the direct azidooxygenation of alkenes giving azidohydroxy derivative 4 using excess amount of N 3 -I(III) reagent and TEMPONa as N-and O-nucleophiles, respectively, thus requiring additional steps to achieve 1,2-azidoalcohols. 19 N,N-Dimethylformamide is a popular formylating agent; 20 however, its role in nucleophilic substitution reactions is quite rare 21 and opens up a new area of research that is yet to be established. For the first time, we have reported the controlled synthesis of either regioisomers of 1,2-azidoalcohols with high diastereomeric ratios using DMF as the O-nucleophile or NaN 3 as the N-nucleophile (Scheme 1).…”
mentioning
confidence: 99%
“…in DMF : DMSO : H 2 O (1 : 1 : 0.4) gave 3a in 54% yield suggesting the formation of the cyclic intermediate III, which can account for the reversal in regio-and stereoselectivity of azidohydroxylation under the aqueous conditions. Based on the above experiments and literature precedence, 18,21 the above mechanism has been proposed (Scheme 3). Initially, alkene reacts with iodine to form the iodonium ion which undergoes regioselective ring opening with DMF to give the corresponding iodo intermediate I followed by a subsequent stereoselective displacement with the azide ion to form species II.…”
mentioning
confidence: 99%